2010
DOI: 10.1016/j.exger.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urodynamic effects of phytoestrogens equol, puerarin and genistein with these of estradiol 17β in ovariectomized rats

Abstract: Comparison of urodynamic effects of phytoestrogens equol, puerarin and genistein with these of estradiol 17β in ovariectomized rats. Experimental Gerontology, Elsevier, 2010, 45 (2) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…All of these changes elicited by puerarin were consistent with but weaker than 17β‐estradiol (E 2 ). These results demonstrate that puerarin could ameliorate urethral closure, which might be beneficial to the treatment of postmenopausal urge incontinence (Thielemann et al ., ). Puerarin markedly elevated weight, IGF‐1 and C3 expression, progesterone receptor mRNA levels in uterine, and the level of total antioxidant capacity in serum, whereas it attenuated MDA and lymphocytes DNA damage in ovx rats, suggesting that puerarin has uterotropic effects and might be an effective therapeutic agent against endometrial hyperplasia and premenstrual syndrome (Rachoń et al ., ; Tang et al ., ).…”
Section: Pharmacological Actionsmentioning
confidence: 97%
“…All of these changes elicited by puerarin were consistent with but weaker than 17β‐estradiol (E 2 ). These results demonstrate that puerarin could ameliorate urethral closure, which might be beneficial to the treatment of postmenopausal urge incontinence (Thielemann et al ., ). Puerarin markedly elevated weight, IGF‐1 and C3 expression, progesterone receptor mRNA levels in uterine, and the level of total antioxidant capacity in serum, whereas it attenuated MDA and lymphocytes DNA damage in ovx rats, suggesting that puerarin has uterotropic effects and might be an effective therapeutic agent against endometrial hyperplasia and premenstrual syndrome (Rachoń et al ., ; Tang et al ., ).…”
Section: Pharmacological Actionsmentioning
confidence: 97%
“…Ovariectomised rats are commonly used as a model to emulate human menopause (Diep and Contantinou 1999). The phytoestrogens that are present in soy bind both oestrogen receptors α and β (Morito et al 2001), and phytoestrogens have been shown to be effective as β-estradiol for improving bladder function in ovariectomised rats (Thielemann et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…No subjective improvement over urinary complaints were found in our study despite the fact that isoflavones have shown positive effects on the urethral sphincter mechanism in the animal model [49] and in patients with prostate carcinoma [50]. The latter clinical study [50], however, used a rather high isoflavone dose (200 mg/day for 6 months).…”
Section: Discussionmentioning
confidence: 65%